2010
DOI: 10.1093/ndt/gfq411
|View full text |Cite
|
Sign up to set email alerts
|

Serum IL-6, albumin and comorbidities are closely correlated with symptoms of depression in patients on maintenance haemodialysis

Abstract: Maintenance haemodialysis patients with symptoms of depression may have higher serum IL-6 and lower serum albumin levels. The prevalence of depression was lower in elderly patients at or above 75 years old, and no correlation was found with socio-economic status. Factors including co-morbid conditions, serum IL-6, albumin and age may help predict which patients may be predisposed to develop symptoms of depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
60
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 35 publications
6
60
1
Order By: Relevance
“…Those with DS had higher interleukin-6 and lower albumin levels. 28 No association between hs-CRP and serum albumin level was observed in the present cohort. Cilan et al reported higher concentrations of pro-inflammatory cytokines in an HD population compared with a control group; however, no significant difference between patients with or without DS was demonstrated.…”
contrasting
confidence: 61%
“…Those with DS had higher interleukin-6 and lower albumin levels. 28 No association between hs-CRP and serum albumin level was observed in the present cohort. Cilan et al reported higher concentrations of pro-inflammatory cytokines in an HD population compared with a control group; however, no significant difference between patients with or without DS was demonstrated.…”
contrasting
confidence: 61%
“…Similar results to what we found in this study have recently been reported by Hung et al (2011), who explored the relationship between depression and demographic, socio-economic and clinical variables in CKD patients [12]. In another study, Wuerth et al (2003) screened chronic peritoneal dialysis (PD) patients from July 1997 to October 2002, using the Beck Depression Inventory questionnaire.…”
Section: Discussionsupporting
confidence: 89%
“…A recent study showed strong associations between depression, inflammation, and serum albumin in maintenance dialysis patients (75). It is recommended that patients with ESRD be screened at the initiation of dialysis therapy, within 3-6 months after therapy initiation, and then yearly using depression screening self-report questionnaires, such as the Beck Depression Inventory.…”
Section: Summary and Recommendationsmentioning
confidence: 99%